The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1126/science.3388021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Estrogen Receptors in Normal Human Osteoblast-Like Cells

Abstract: In seven strains of cultured normal human osteoblast-like cells, a mean of 1615 molecules of tritium-labeled 17 beta-estradiol per cell nucleus could be bound to specific nuclear sites. The nuclear binding of the labeled steroid was temperature-dependent, steroid-specific, saturable, and cell type-specific. These are characteristics of biologically active estrogen receptors. Pretreatment with 10 nanomolar estradiol in vitro increased the specific nuclear binding of progesterone in four of six cell strains, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
227
2
10

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,154 publications
(250 citation statements)
references
References 21 publications
7
227
2
10
Order By: Relevance
“…A wide distribution of ER␣-immunoreactions has been reported in primate dermal fibroblasts (Bentley et al, 1986); human fibroblasts; human endothelial cells (Brandi et al, 1993); mammary gland cells (for review, see Pelletier, 2000); chondrocytes in cows, pigs, and humans (Claassen et al, 2001); human osteoblasts (Eriksen et al, 1988); and human osteoclasts (Pensler et al, 1990), in addition to female reproductive tissues, indicating that estrogen has diverse effects on development, growth, and homeostasis (Clark et al, 1992). Although many epidemiological studies have reported a higher frequency of TMD in females than in males (Campbell et al, 1993; LeResche, 1997; Kapila and Xie, 1998), there has been controversy concerning the presence of ER␣ in the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…A wide distribution of ER␣-immunoreactions has been reported in primate dermal fibroblasts (Bentley et al, 1986); human fibroblasts; human endothelial cells (Brandi et al, 1993); mammary gland cells (for review, see Pelletier, 2000); chondrocytes in cows, pigs, and humans (Claassen et al, 2001); human osteoblasts (Eriksen et al, 1988); and human osteoclasts (Pensler et al, 1990), in addition to female reproductive tissues, indicating that estrogen has diverse effects on development, growth, and homeostasis (Clark et al, 1992). Although many epidemiological studies have reported a higher frequency of TMD in females than in males (Campbell et al, 1993; LeResche, 1997; Kapila and Xie, 1998), there has been controversy concerning the presence of ER␣ in the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrations that cells of the osteoblastic lineage, which include osteoblasts and osteocytes in bone and osteoblast progenitor cells in sites such as the bone marrow stroma, express both a and p isoforms of the estrogen receptor [7,10,38] have suggested that many effects of E?. on bone are mediated through actions on these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Vários trabalhos não evidenciam a presença de receptores de E2 nos osteoclastos (13), mas sim nos osteoblastos (14) e em células do estroma da medula óssea (15). Assim, o aumento da reabsorção óssea conseqüente à carência estrogênica pode ser secundário a um aumento da secreção pelos osteoblastos ou pelas células do estroma da medula óssea de fatores capazes de estimular osteoclastos e/ou seus precursores, resultando em aumento da reabsorção óssea.…”
Section: Osteoporose Pós-menopausa (Tipo I)unclassified